Anarchy, State, and Property - Lindblom, Lars; Justus Liebig University Giessen (My University, 2014)
The fundamental function of the state is safeguarding the safety of its citizens. The combination of Nozick's invisible hand explanation with his theory of justice implies that individuals can have full private property rights in the state. An individual with such property rights thus has the right to sell and destroy what he or she owns. This implies that it is perfectly fair to buy a state and dismantle it, thereby leaving citizens without protection. I conclude that Nozick's theory of the state fails since it cannot guarantee the protection of its citizens' safety.
Keywords: the state; invisible hand explanation; property; Nozick; security; ddc:100; ddc:330